Quasi-Complete Response of Classic Kaposi’s Sarcoma Treated with Weekly Paclitaxel - Zineb Benbrahim; Samia Arifi; Hafida Benhammane; Kaoutar Inani; Salim Gallouj; Meriem Meziane; Fatima Zahra Mernissi; Nawfel Mellas; Omar El Mesbahi (Case Reports in Oncological Medicine)
Classic Kaposi’s sarcoma (CKS) is a subtype that traditionally occurs in elderly HIV-negative males of Mediterranean origin. Patients with CKS characteristically present with skin lesions in the distal extremities. Involvement of the viscera is uncommon but may occur in the late stages of the disease. Patients with extensive KS can be treated with systemic chemotherapy. A number of drugs approved for treatment of AIDS-associated KS, especially Paclitaxel, have activity against CKS after failure of prior therapy. We report a patient treated with weekly Paclitaxel, as initial chemotherapy, for CKS presenting with multiple visceral involvement and having a contraindication for Bleomycin. The patient had quasi-complete response after three months of chemotherapy suggesting that weekly Paclitaxel might be effective as a first-line therapy for classical type KS with visceral involvement.